Museus e “Aprofundamento Da Democracia” – É Possível Pensá-los, Fazê-los, Sustentá-los? - Estêvão, Florbela (Trabalhos de Antropologia e Etnologia, 2020)
This paper aims to think the role of museums – considered in a broad sense – within contemporary society, as an increasingly globalized world, characterised by all kinds of crescent asymmetries. Consequently, museums face today permanently new challenges in this context where they must clearly assume their political role, leading us to consider how we can contribute through them to a more democratic and inclusive societal life, in which all citizens could be able to play an active role, being not mere visitors and spectators of museum collections and narratives produced by museum experts.